Factors influencing the successful adoption of mobile commerce services - De Sousa, Sergio Anthony David (Rhodes University, Faculty of Commerce, Department of Information Systems, 2013)
Mobile Commerce (MC) can be defined as any transaction carried out over a wireless network, using a wireless device, such as a mobile phone, and that has monetary value (Wang and Liao, 2007). MC is a rapidly developing industry in tenns of its technological capabilities. With these increasing developments, come greater forecasts of potential benefits to societies, economies, industries and individuals. However, the growth and development ofthe underlying MC technology, has not been met by the creation and adoption of the services meant to accompany MC. It is said that the success of MC will ultimately lie in its services. As MC Service Providers (MCSP) are responsible for delivering these MC Services (MCS), the success ofMC can be said to rest on them. In order for MCSs to be successfully adopted, both the initial use and continuous use thereof should be targeted. In other words those that have used MCSs (users) and those that have yet to use MCSs (non-users) should be targeted. It is thus pivotal that an understanding of the factors that generate MCS adoption be sought. This research purposed to uncover the factors that generate MCS adoption within the user and nonuser group. In defining successful adoption ofMCS's, two separate measures were used for each group. User satisfaction is a well accepted construct among researchers for measuring system success among users. User satisfaction is also accepted to be a detenninant of service re-use and loyalty. Intention to use is a measure used for MC success among non-users and is accepted to be a detenninant of actual use. Factors affecting both detenninants, user satisfaction and intention to use, were investigated. After a review ofliterature and current models, ten (10) factors were hypothesised to be significant factors in determining user satisfaction and intention to use namely: ease of use, cost, speed, personalisation, pennission, privacy, security, convenience, relationship (with MCSP) and awareness. A questionnaire was developed to test the hypothesised factors. Not all factors were proven to have a significant impact on both user satisfactions and intention to use. One main recommendation is that both initial and continuous adoption should be the focus ofMC strategy. Services that cater to specific user needs and offer convenience at a low cost should be offered. MCSPs can use the factors proved to be significant to generate and evaluate their service offering, to users and non users, to increase the probability of successful adoption from initial to continuous use. The research concludes that MCSPs need to begin to offer MCSs that meet user needs and add value to their lives in order to realise the professed potential ofMC.
Keywords: Mobile commerce; Electronic commerce; Wireless communication systems; Mobile communication systems; Computer networks